Modern tendencies of organization of building production in the conditions of dense urban development - Аrutiunian I.; Banakh А.; Аrutiunian Ye. (Ways to Improve Construction Efficiency, 2020)
In the article the problems of construction in dense urban areas based on the analysis of scientific and directive sources of foreign and domestic scientists and specialists are determined. In the world, on the one hand, a large number of solutions have been proposed, certain architectural and design techniques have been worked out, that have an undoubted interest for architects, and on the other hand, many problems with architectural, planning and design aspects of dense urban development and whole modern city structure have arisen. It has affected our country. Today there is a tendency to increase the volumes of new construction and reconstruction in the conditions of dense urban development due to changes in the segmentation of demographic and geographical markers of the economic and political situation in Ukraine. There is an increasing of the intensity of construction works in the central parts of large cities and other settlements. It is a feature of modern urban engineering in the tendency of spatial planning and development. Therefore, there is an urgent need for rational methods of organization of building production and building processes. Current trends allow to improving organization processes through the application of logistics approaches. Logistics is a modern mechanism that determines the ways of updating the methods of building processes organization and able to successfully solve the most significant problems due to reliable flow control within the limits of material and production parts of the building companies activities. The main goal of building processes organization in urban areas can be achieved with the logistics concepts such as “exactly – in time”, “needs / resources planning”, “OРT”. It gives a fundamental rethinking of the theory and practice of building production in the cases of new construction, reconstruction, ongoing or scheduled maintenances in built-up areas, landscape planning units, etc. It also allow to define the need of daily maintenance facilities in built-up area, as well as the size of land plots for new construction compliant with urban planning and engineering directives, sanitary standards and fire safety requirements.